Tuberous Sclerosis Associated Neuropsychiatric Disorders (TAND) and the TAND Checklist - de Vries, Petrus J.; Whittemore, Vicky H.; Leclezio, Loren; Byars, Anna W.; Dunn, David; Ess, Kevin C.; Hook, Dena; King, Bryan H.; Sahin, Mustafa; Jansen, Anna (Pediatric neurology, 2015)
Tuberous sclerosis complex is a multisystem genetic disorder with a range of physical manifestations that require evaluation, surveillance, and management. Individuals with tuberous sclerosis complex also have a range of behavioral, psychiatric, intellectual, academic, neuropsychologic, and psychosocial difficulties. These may represent the greatest burden of the disease. Around 90% of individuals with tuberous sclerosis complex will have some of these difficulties during their lifetime, yet only about 20% ever receive evaluation and treatment. The Neuropsychiatry Panel at the 2012 Tuberous Sclerosis Complex International Consensus Conference expressed concern about the significant “treatment gap” and about confusion regarding terminology relating to the biopsychosocial difficulties associated with tuberous sclerosis complex. The Tuberous Sclerosis Complex Neuropsychiatry Panel coined the term TAND—tuberous sclerosis complex-associated neuropsychiatric disorders—to bring together these multidimensional manifestations of the disorder, and recommended annual screening for TAND. In addition, the Panel agreed to develop a TAND Checklist as a guide for screening. Here, we present an outline of the conceptualization of TAND, rationale for the structure of the TAND Checklist, and include the full US English version of the TAND Checklist. We hope that the unified term TAND and the TAND Checklist will raise awareness of the importance of tuberous sclerosis complex-associated neuropsychiatric disorders and of the major burden of disease associated with it, provide a shared language and a simple tool to describe and evaluate the different levels of TAND, alert clinical teams and families or individuals of the importance of screening, assessment, and treatment of TAND, and provide a shared framework for future studies of tuberous sclerosis complex-associated neuropsychiatric disorders.